Difference in Strigasusceptibility is reflected in strigolactone secretion profile, but not in compatibility and host preference in arbuscular mycorrhizal symbiosis in two maize cultivars - Yoneyama, K.; Arakawa, R.; Ishimoto, K.; Kim, H.I.; Kisugi, T.; Xie, X.; Nomura, T.; Kanampiu, F.K.; Yokota, T.; Ezawa, T. (Wiley, 2015)
Strigolactones released from plant rootstrigger both seed germination of parasitic weeds such as Striga spp. and hyphal branching of the symbionts arbuscular mycorrhizal (AM) fungi. Generally, strigolactone composition in exudates is quantitatively and qualitatively different among plants, which may be involved in susceptibility and host specificity in the parasite – plant interactions. We hypothesized that difference in strigolactone composition would have a significant impact on compatibility and host specificity/preference in AM symbiosis.